Lignin oxidation and depolymerisation in ionic liquids. Issue 3 (25th September 2015) - Prado, R.; Brandt, A.; Erdocia, X.; Hallet, J.; Welton, T.; Labidi, J.
Abstract : The depolymerisation of lignin directly in the black liquor was studied, comparing two ionic liquids as extracting solvents (butylimidazolium hydrogen sulphate and triethylammonium hydrogen sulphate), under oxidising conditions. Abstract : The depolymerisation of lignin directly in the black liquor was studied, comparing two ionic liquids as extracting solvents (butylimidazolium hydrogen sulphate and triethylammonium hydrogen sulphate), under oxidising conditions. H2 O2 was chosen as the oxidant agent. It was observed that lignins derived from butylimidazolium hydrogen sulphate were more susceptible to degradation. The main degradation products found in the extracted oils were aromatic acids, such as vanillic acid, benzoic acid and 1, 2-benzenedicarboxylic acid.